Pengembangan Media Pembelajaran Bola Basket Kelas 10 Berbasis Android - Kiswanto, Kiswanto; Nasuka, Nasuka; Hidayah, Taufiq; Wahyudi, Agung (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
T The purpose of this study is to develop android-based basketball learning media for grade X students. This research method uses the Borg and Gall development procedure consisting of 10 steps. However, in this development research, several stages are used, namely; analyzing the product to be developed; developing the initial product; expert validation;small-scale field trials; product revision; expert validation; large-scale trials; product feasibility test. The results of this study are the results of material expert validation with an overall average validation result of 87.5%, media expert validation results with an overall average validation result of 78.5%, Phase I trial results (small group) with a percentage result of 85%, Phase II trial assessment results (large group) with a percentage result of 88%. Conclusion, the development of android-based basketball learning media can be used on basketball material. Keywords: Applications, Basketball, Learning Media,.